The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/jrfm15020041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on International Trade among the Visegrad Countries

Abstract: The impact of the COVID-19 pandemic has been detrimental toall countries, despite the continuous efforts of governments on all continents to attempt to mitigate its damaging effects. All economic and social indicators have worsened. This study explores the impact of COVID-19 on international trade among the Visegrad Four (V4) countries. We employ data from Eurostat and FRED to explore this influence, using the monthly import and export data for the 2010 M1–2021 M4period. We estimate the trade model for each me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Thus, the findings based on the effects of COVID-19 show that the tightening measures taken to mitigate the hitches of COVID-19 have a significant contractionary impact on exports. Our empirical findings in terms of the trade impacts of COVID-19 are in line with Che et al ( 2020 ), Hayakawa and Imai ( 2021 ), Zhao et al ( 2021 ), Hayakawa and Mukunoki ( 2021 ), Liu et al ( 2021 ), and Ugurlu and Jindřichovská ( 2022 ).…”
Section: Estimation Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the findings based on the effects of COVID-19 show that the tightening measures taken to mitigate the hitches of COVID-19 have a significant contractionary impact on exports. Our empirical findings in terms of the trade impacts of COVID-19 are in line with Che et al ( 2020 ), Hayakawa and Imai ( 2021 ), Zhao et al ( 2021 ), Hayakawa and Mukunoki ( 2021 ), Liu et al ( 2021 ), and Ugurlu and Jindřichovská ( 2022 ).…”
Section: Estimation Resultssupporting
confidence: 90%
“…Ugurlu and Jindřichovská ( 2022 ), tried to discover the impact of COVID-19 on international trade using the ARDL method for Visegrad Four (V4) countries using the monthly data from 2010M1 to 2021M4. They found that while the COVID-19 affected trade relations of these countries, its impacts vary among countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the past decade, the world's leading governments, international financial institutions, and the players in the banking system have sought to address the economic (financial, banking, and accounting) problems of the 2007/2008 crisis, accompanied by strong monetary policy expansion and, after some consolidation, the coronavirus crisis posed new challenges to the world economy, including national economies and businesses alike. Several authors found that the COVID-19 impact was evident in all countries, but not with the same strength (Juergensen et al 2020;Nieto and Rubio 2022;Ugurlu and Jindřichovská 2022;Zainal et al 2022). We witnessed strong government intervention in all parts of the world.…”
Section: Introductionmentioning
confidence: 84%
“…According to [16], the concept of Total Quality Management should include (Figure 2): According to [17], the effectiveness of Total Quality Management in an industrial enterprise can be determined based on the criteria (Figure 3): According to [18] , for the effective use of Total Quality Management, it is advisable: 1) To involve the company's personnel more widely to ensure quality control of the products produced. The degree of interest of the company's personnel in improving the quality of its products…”
Section: Introductionmentioning
confidence: 99%